Frontiers in hybrid and interfacial materials chemistry research. (November 2020) - Guiton, Beth S.; Stefik, Morgan; Augustyn, Veronica; Banerjee, Sarbajit; Bardeen, Christopher J.; Bartlett, Bart M.; Li, Jun; López-Mejías, Vilmalí; MacGillivray, Leonard R.; Morris, Amanda; Rodriguez, Efrain E.; Samia, Anna Cristina S.; et al.
Abstract: Abstract : Through diversity of composition, sequence, and interfacial structure, hybrid materials greatly expand the palette of materials available to access novel functionality. The NSF Division of Materials Research recently supported a workshop (October 17–18, 2019) aiming to (1) identify fundamental questions and potential solutions common to multiple disciplines within the hybrid materials community; (2) initiate interfield collaborations between hybrid materials researchers; and (3) raise awareness in the wider community about experimental toolsets, simulation capabilities, and shared facilities that can accelerate this research. This article reports on the outcomes of the workshop as a basis for cross-community discussion. The interdisciplinary challenges and opportunities are presented, and followed with a discussion of current areas of progress in subdisciplines including hybrid synthesis, functional surfaces, and functional interfaces.